2019
DOI: 10.5194/amt-2019-139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intercomparison of nitrous acid (HONO) measurement techniques in a megacity (Beijing)

Abstract: Nitrous acid (HONO) is a key determinant of the daytime radical budget in the daytime boundary layer, with quantitative measurement required to understand OH radical abundance. Accurate and precise measurements of HONO are therefore needed; however HONO is a challenging compound to measure in the field, in particular in a chemically complex and highly polluted environment. Here we report an inter-comparison exercise between HONO measurements performed by 30 two wet chemical techniques (the commercially availab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Intercomparison in the NCP between various HONO measurement techniques also confirmed the reliability of LOPAP to quantify HONO in the polluted regions. 34,36,37 Other instruments for key-related species (VOCs, OVOCs, NO, NO2, NH3, O3, H2O2, CO, PM2.5, particle size distribution, and composition, etc.) and meteorological parameters (pressure, temperature, relative humidity (RH), J(NO2), etc.)…”
Section: Field Measurementsmentioning
confidence: 99%
“…Intercomparison in the NCP between various HONO measurement techniques also confirmed the reliability of LOPAP to quantify HONO in the polluted regions. 34,36,37 Other instruments for key-related species (VOCs, OVOCs, NO, NO2, NH3, O3, H2O2, CO, PM2.5, particle size distribution, and composition, etc.) and meteorological parameters (pressure, temperature, relative humidity (RH), J(NO2), etc.)…”
Section: Field Measurementsmentioning
confidence: 99%
“…However, it should be noted that in some reported SIFT-MS studies very large sample flow rates were used (in order to enhance analytical sensitivity) when the above phenomenon must become more problematic. 4,5 In this major part of this study there are the primary ternary association reactions of three reagent ions, R + , with three different…”
Section: Methodsmentioning
confidence: 99%
“…Photodissociation of HONO produces the hydroxyl radical (OH); this pathway can be a more important OH radical source (>10 times greater) than the photolysis of O3 to O( 1 D) and subsequent 25 reaction with water, especially in polluted urban environments (Harrison et al, 1996;Ren et al, 2006;Alicke et al, 2002). Despite the importance of HONO, accurate and time-resolved (i.e., < 5 min) in situ measurements of ambient HONO mixing ratios remain a challenge, exemplified by discrepancies reported among individual instruments in recent inter-comparison studies (Rodenas et al, 2013;Pinto et al, 2014;Crilley et al, 2019). These discrepancies arise in part as atmospheric HONO measurements by wet 30 chemical techniques or mass spectrometry require external calibration and are prone to interferences.…”
Section: Introductionmentioning
confidence: 99%
“…Other sources of systematic error in IBBCEAS instruments include the determination of the mirror reflectivity curve and, if purge gases are used to prevent contact of the sampled gas with the mirrors, the length over which the absorber is present (d0) compared to the total optical pathlength (d) (Duan et al, 2018). To exemplify these challenges, a recent inter-comparison study 60 (Crilley et al, 2019) has revealed significant biases in the retrieved mixing ratios between two modern IBBCEAS instruments, implying that IBBCEAS instruments must be validated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation